Experimental Investigation of the Fatigue Lifespan of Anchor Bolts with Consideration of Loading History - Miroslav Pástor; Pavol Lengvarský; Martin Hagara; Alžbeta Sapietová; Patrik Šarga (Applied Sciences, 2021)
Preloaded bolted connections are one of the most used approaches for anchoring steel structures and equipment. Preload is induced by a mechanical tightening of the nut with the required torque. In the case of anchor bolts embedded in a concrete base, the prescribed tightening procedure has to be followed for safe and reliable operation. The present paper addresses the problem of anchoring a new casting pedestal using the original anchor bolts. The aim was to verify the original anchoring system’s reliable and safe operation, taking into account the current condition of the bolts. The analysed anchoring bolts are subjected to cyclic (disappearing) stress during the rotation of the casting pedestal. If the interplays between the anchor bolt and the concrete foundation were damaged, production would shut down, resulting in high economic losses. For this reason, the authors used a modified nut with a lightened first thread when investigating the actual state of the anchoring and setting the required preload. The shape and dimensions of the nut were determined based on the results of numerical modelling. The experimental measurements consisted of two phases. In the first phase, the values of axial forces in the anchor bolts at the required preload were set using the designed dynamometers. The second phase was focused on the operational measurements. The methodology of measuring the axial forces and the interpretation of the results obtained, including a comprehensive view of the anchoring safety, provides relevant evidence of the functionality and effectiveness of the proposed solution. Based on the results of the operational measurement and the prescribed handling of the casting pedestal, the lifespan of the anchoring was determined to be 3650 days under the loading cycles to date.